HUBUNGAN PAJANAN PESTISIDA MASA KEHAMILAN DENGAN GANGGUAN PERKEMBANGAN ANAK PRA SEKOLAH (4-5 TAHUN) DI DESA SUMBEREJO KECAMATAN NGABLAK KABUPATEN MAGELANG - Winnoto Winnoto; Yusniar Hanani Darundiati; Onny Setiani (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
In the agriculture field, farmers are a demand to get results high qualities and large quantities on a fast scale. Ngablak sub-district is one of the districts with the vast agricultural area. The primary job of Ngablak’s people is farmers. The using of pesticide which it was so high and intensive would increase the agriculture production. The other impact is can be harmful to human health and the environment. The children who get exposed to pesticides has more often disruption of child development. This study aimed to analysis the relationship of pregnancy pesticide exposure with pre-school children’s (4-5 years) development disorders in the Sumberejo village Ngablak district of Magelang regency. The study used observational design with cross-sectional approach. The total number of samples 25 respondents selected by purposive, carried on the Sumberejo village Ngablak district of Magelang regency. The instruments used were the props and Ages and Stages questionnaire by Bricker D., Squires J., and Twombly E., which has been modified. Analysis used by Chi Square. The children with development disorders there are 64%. The results of Chi Square analysis showed that there was relationship of pesticide exposure the frequency of pesticide spraying (pvalue= 0,017), duration of pesticides exposure (pvalue= 0,004), Mixing Pesticides (pvalue= 0,041), location of residence (pvalue = 0.002) and the use of PPE (pvalue= 0,041). Variables that there is no correlation (p> 0.05) which is a source of clean water (pvalue = 0.116) and storage of pesticides (pvalue = 0.200). The conclusion of this study there are relationships between the frequency of pesticide spraying, long exposure to pesticides, pesticide mixing, the location of residence and use of PPE in pregnancy with pre school children’s (4-5 years) development disorders in Sumberejo village Ngablak district of Magelang regency.